Groundwater dynamics and hydrogeological processes in the Alter do Chão Aquifer: A case study in Manaus, Amazonas – Brazil - Brito, Alderlene Pimentel de; Manzione, Rodrigo Lilla [UNESP]; Wahnfried, Ingo Daniel (Elsevier, 2025)
Fluctuations in groundwater levels can occur for several reasons related to hydrological, geological, climatic, or even anthropogenic influences due to aquifer exploitation and land use change. In Manaus, the capital of the State of Amazonas, in Brazil, the Alter do Chão Aquifer (ACA) is the main source for private water supply. The recent extreme droughts that affected the Amazon region confirmed the relevance and importance of the ACA water reserves, which must be better understood and studied to promote effective, balanced, and informed groundwater resources management. Even with a monitoring network spread over the city collecting continuous data, information about groundwater levels is not effectively used for water management purposes. Understanding the levels variations, the dynamics of groundwater and the factors that influence groundwater behaviour becomes fundamental in times of water crisis, scarcity, and intensification of extreme climatic events. The objective of this work was to understand the behaviour of groundwater levels in the ACA to determine the main factors influencing groundwater reserve fluctuations under different stresses. Four wells monitored between 2010 and 2023 were analysed using physical-based time series models. The models incorporated time series of precipitation, evapotranspiration, river stage and linear trends from climatological events that occurred in certain periods as multiple inputs and possible stresses in the ACA reserves. The results demonstrate that the ACA presents fast responses to climatological inputs. Even located in the same hydrogeological context, the wells reveal different responses to precipitation and evapotranspiration, the major factors of influence. Also, significant trends were found during El Niño (2014–2016) and La Niña (2020–2023) events. This information can be used for planning water use, understanding the mechanisms of recharge and discharge of groundwater, for drilling new wells and exploring new areas with potential for economic and social growth, in line with environmental preservation.
Keywords: Amazonia; Impact-drivers; Monitoring; Time series modelling